Zuhud dan Etos Kerja Pengamal Tarekat Naqsyabandiyah Khalidiyah: Asceticism and Work Ethic of the Practitioners of the Naqshbandiyah Khalidiyah Order - Mahmudah Mahmudah (Fenomena, 2007)
The widespread assumption that Sufi asceticism (zuhud) leads to worldly detachment and laziness has created a negative image of Sufi communities. This study examines the influence of zuhud on the work ethic among practitioners of the Naqsabandiyah Khalidiyah Tarekat at Surau Ghausil Amin I, Jember. Grounded in Islamic spiritual ethics and Max Weber’s distinction between mysticism and asceticism, the research aims to determine whether zuhud affects followers’ work productivity positively or negatively. A qualitative approach was employed, using interviews and documentary analysis, with data analyzed in a descriptive-reflective manner. The findings reveal that, as understood by the practitioners, zuhud does not mean renouncing the world or avoiding productive work. Instead, it signifies a mental state of not being overly attached to wealth and worldly pleasures while remaining devoted to Allah. Consequently, this concept fosters a strong work ethic, as followers view worldly life as a means to prepare for the hereafter and work sincerely for divine blessing. The study concludes that zuhud positively influences work ethic and recommends further research on Sufi orders’ contributions to economic productivity. Anggapan luas bahwa zuhud dalam tasawuf menyebabkan pengasingan diri dari dunia dan kemalasan telah menciptakan citra negatif terhadap komunitas sufi. Penelitian ini mengkaji pengaruh zuhud terhadap etos kerja pengamal Tarekat Naqsabandiyah Khalidiyah di Surau Ghausil Amin I, Jember. Berlandaskan etika spiritual Islam dan perbedaan tipologi Weber antara mistisisme dan asketisme, penelitian ini bertujuan mengetahui apakah zuhud berpengaruh negatif atau positif terhadap produktivitas kerja pengikut tarekat. Metode kualitatif digunakan melalui wawancara dan dokumentasi, dengan analisis deskriptif-reflektif. Hasil penelitian menunjukkan bahwa zuhud bagi pengamal tarekat tidak berarti meninggalkan kehidupan dunia atau anti kemewahan, melainkan kondisi mental tidak terpengaruh oleh harta dan kesenangan duniawi dalam beribadah kepada Allah. Konsep ini justru memperkuat etos kerja karena mereka memandang dunia sebagai bekal menuju akhirat, bekerja dengan niat ikhlas mencari ridha Allah. Kesimpulannya, zuhud berpengaruh positif terhadap etos kerja. Penelitian lanjutan tentang kontribusi tarekat terhadap produktivitas ekonomi direkomendasikan.